Case Report: Myocardial Bypass in Left Descending Artery - A Rare Congenital Anomaly - Carvalho,Vergílio Pereira (2020)
Abstract Myocardial bypass (MB) is known to have scientific relevance and is present in several studies with great statistical significance regarding its clinical manifestations and complications. There are still questions about MB in its relationship with heart disease and repercussion in life-threatening conditions. We present a case report of a MB in the left anterior descending coronary artery, whose objective is to identify this rare congenital anomaly and to highlight the patient's clinical outcome in order to elicit greater contributions about the presence of this variant in the emergency room, its diagnosis by angiography and therapeutic management.